Involvement of dopamine receptors in diethylpropion-induced conditioning place preference - Planeta,C.S. (1998)
Diethylpropion (DEP) is an amphetamine-like agent used as an anorectic drug. Abuse of DEP has been reported and some restrictions of its use have been recently imposed. The conditioning place preference (CPP) paradigm was used to evaluate the reinforcing properties of DEP in adult male Wistar rats. After initial preferences were determined, animals weighing 250-300 g (N = 7 per group) were conditioned with DEP (10, 15 or 20 mg/kg). Only the dose of 15 mg/kg produced a significant place preference (358 ± 39 vs 565 ± 48 s). Pretreatment with the D1 antagonist SCH 23390 (0.05 mg/kg, sc) 10 min before DEP (15 mg/kg, ip) blocked DEP-induced CPP (418 ± 37 vs 389 ± 31 s) while haloperidol (0.5 mg/kg, ip), a D2 antagonist, 15 min before DEP was ineffective in modifying place conditioning produced by DEP (385 ± 36 vs 536 ± 41 s). These results suggest that dopamine D1 receptors mediate the reinforcing effect of DEP